2015
DOI: 10.1116/1.4933089
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature atomic layer deposition of copper(II) oxide thin films

Abstract: Copper(II) oxide thin films were grown by atomic layer deposition (ALD) using bis-(dimethylamino-2-propoxide)copper [Cu(dmap)2] and ozone in a temperature window of 80–140 °C. A thorough characterization of the films was performed using x-ray diffraction, x-ray reflectivity, UV-Vis spectrophotometry, atomic force microscopy, field emission scanning electron microscopy, x-ray photoelectron spectroscopy, and time-of-flight elastic recoil detection analysis techniques. The process was found to produce polycrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…This problem might be possibly overcome by incorporation of polymers like Nafion as reported in the literature . Moreover, we envisage that further improvements in sensitivity and detection limit can be achieved if the morphology of CuO is optimized for larger electrochemically active surface area and better light absorption, for example by depositing conformal CuO film onto ITO nanocrystals by atomic layer deposition . Finally, our results show that a careful analysis is necessary for realistic evaluation of distinct advantages associated with operation of sensors based on nanostructured semiconductors in either electrochemical or photoelectrochemical mode.…”
Section: Discussionmentioning
confidence: 99%
“…This problem might be possibly overcome by incorporation of polymers like Nafion as reported in the literature . Moreover, we envisage that further improvements in sensitivity and detection limit can be achieved if the morphology of CuO is optimized for larger electrochemically active surface area and better light absorption, for example by depositing conformal CuO film onto ITO nanocrystals by atomic layer deposition . Finally, our results show that a careful analysis is necessary for realistic evaluation of distinct advantages associated with operation of sensors based on nanostructured semiconductors in either electrochemical or photoelectrochemical mode.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that the growth rate slowed down after reaching a full coverage of the substrate. Cu(dmap) 2 has been employed as a precursor also in other ALD processes of copper metal [ 21–22 ] as well as of copper(I) oxide, [ 23 ] copper(II) oxide, [ 24 ] and hybrid copper‐organic material. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
“…Among these process modules, ALD has advantages for device manufacturing because it produces conformal films with good spatial uniformity at relatively low processing temperatures. ALD is based on self-limiting surface chemical reactions, which enables precise control of film thickness and composition. , While a wide range of studies have reported ALD of Cu metal, a narrower set of papers have explored ALD of CuO x . , Thermal ALD of Cu 2 O and CuO thin films has been previously reported, where control over the phase and bulk oxidation state was achieved using ozone and water coreactants with a bis­(dimethylamino-2-propoxide)­copper­(II) [Cu­(dmap) 2 ] precursor . Control of crystallinity and morphology in copper oxide deposited by thermal ALD has also been achieved by varying the deposition temperature or the number of ALD cycles using a range of precursors. …”
Section: Introductionmentioning
confidence: 99%